Peningkatan Perilaku Hidup Bersih dan Sehat melalui Manajemen Pemilahan Sampah Rumah Tangga: Increasing Clean and Healthy Living Behavior through Household Waste Sorting Management - Syahruramdhani, Syahruramdhani; Indriastuti, Nur Azizah; Mubarrok, Zennul; Ramadhani, Vita Listya Putri; Authoria, Indira Nailul; Efhiliana, Yuanita; Izzati, Ikfi Mualifa (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Clean and Healthy Living Behavior (PHBS) is a program carried out to achieve good health. One way is to carry out good waste management. Currently, Yogyakarta Province is facing a problem of piling up waste. A lot of waste is generated at home and if it is not managed properly it will cause many problems. Housewives in general do not know how to sort waste and the negative impacts if waste is mixed. This community service program aims to increase public knowledge and awareness, especially among housewives, in carrying out PHBS through sorting household waste. The activity consisted of counseling about PHBS and waste sorting management practices given to 25 housewives in the Teras Baca Jita Kita Learning Community, Bangunjiwo, Kasihan, Bantul, Yogyakarta. The results of this counseling show an increase in participants' understanding of PHBS at home and sorting waste from the post-test results with an average score of 96.4. In addition, participants became increasingly aware of the importance of PHBS and were able to carry out samapha sorting management. It is very important to carry out outreach activities about waste in a sustainable manner and can be followed up with waste processing activities into useful items.